Analgesic therapy and a problem of comorbidity - A. E. Karateev (Современная ревматология)
Analgesic therapy is an essential element of combination treatment in patients with rheumatic diseases (RDs). However, pain killers can cause serious complications. This risk is especially great in patients with comorbidities. Therefore, the individual choice of pharmacological agents for controlling acute and chronic pain in a particular patient largely depends on the presence of comorbidity. This review discusses the incidence of comorbidities in different RDs, the characteristics of adverse reactions from the intake of main analgesics, such as paracetamol, opioids, nonsteroidal anti-inflammatory drugs (NSAIDs), as well as the rational choice of a NSAID in real clinical practice.